Hungarian Monitoring, 23 October 1989 . [Magyar rádiófigyelő], 1989. október 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Shevardnadze and Sakharov on the changes in Hungary - Czechoslovak, GDR and Polish opinions in the context of October 23 - West German reactions - Cult of personality around Erich Honecker - Lithuanian people's front movement Sajudis Domestic Affairs: - Proclamation of the Republic of Hungary - October 23 celebrations - Miklós Németh's call to citizens - Symbolic street name sign change at People's Republic Road - Hungarian Liberal Party formed - National Council of Trade Unions (SZOT) and government representatives confer - Opposition groups' mass rally on Kossuth Square Economy: - South Korean government extends significant credits to Hungary Külpolitika: - Sevardnadze és Szaharov a magyar változásokról - Csehszlovák,NDK, lengyel vélemények a mai nap tükrében - NSZK reakció - Személyi kultusz E. Honecker körül - Szajudisz nevű litván népfront-mozgalom Belpolitika: - A Magyar Köztársaság kikiáltása - Október 23-i emlékünnepségek - Németh Miklós felhívása az állampolgárokhoz - Szimbolikus névtábla csere volt a Népköztársaság útján - Megalakult a Magyar Liberális Párt - Tanácskozás a SZOT és a kormány képviselői között - Ellenzéki szervezetek nagygyűlése a Kossuth téren Gazdaság: - A dél-koreai kormány jelentős hiteleket nyújt Magyarországnak